POLITIK HUKUM TERHADAP KEABSAHAN AKTA NOTARIIL RAPAT UMUM PEMEGANG SAHAM ELEKTRONIK (E-RUPS) PERUSAHAAN BERDASARKAN POJK NOMOR 16/POJK.04/2020 - Alfarijah, Dina Aisyah; Alfaridah, Dini Inasyah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The development of information technology has driven a major transformation in corporate governance, including in the implementation of General Meetings of Shareholders (GMS) of public companies. The Financial Services Authority (OJK) issued OJK Regulation Number 16/POJK.04/2020 concerning the Implementation of Electronic General Meetings of Shareholders of Public Companies (E-GMS) in response to the need for efficiency and the extraordinary conditions of the COVID-19 pandemic. However, there are legal problems regarding the validity of notarial deeds resulting from E-GMS, particularly in the context of fulfilling the authenticity requirements as stipulated in the Notary Law (UUJN). This paper aims to analyze the validity of notarial deeds E-GMS based on the Indonesian positive legal system, as well as review the legal political aspects of the formation of the POJK. The research method used is normative legal research with a statute approach and a conceptual approach. The results of the study indicate that the E-RUPS deed has the potential to lose its authentic nature if it does not fulfill the requirements for the physical presence of the parties as stipulated in Article 16 paragraph (1) letter m of the UUJN, even though it is administratively recognized by the OJK. Therefore, it is necessary to strengthen legal norms that guarantee the authenticity of electronic deeds in the context of digital notaries in the future.